Tlingit houses on beach, Sitka, Alaska, June 1906. - Cobb, John N.
Row of houses along boardwalk of waterfront. Three people, one dog, and a few chickens are in the photo. Canoes are near clothes drying on a line, June 1906. Note from Cobb field notebook: Indian "Ranch," Sitka, Alaska. Note from unidentified source: Houses and boardwalk along beach.